Sanitary quality and treatment of cowpea seeds with essential oil of Lippia lasiocalycina Cham (Research, Society and Development, 2023)
The objective of this work was to evaluate the health quality of cowpea seeds (Vigna unguiculata L. Walp.) used in the Mid-North region of Brazil, to verify the effect of seed treatment with essential oil of Lippia lasiocalycina in the control of fungi in seeds, as well as its effect on germination. Seed health quality was obtained using the Seed Sanity Test (TSS) in 111 samples. To control the microorganisms, the essential oil Lippia lasiocalycina was used, without dilution, in the following concentrations: 0 (without oil); 0.5; 1.0; 2.0; and 4.0 mL Kg-1 of seed. The TSS revealed the presence of Alternaria sp., Aspergilus spp., Cladosporium sp. Curvularia sp., Lasiodiplodia theobromae, Macrophomina phaseolina, Penicillium spp., yeasts, Phoma sp., Fusarium spp, Rhizoctonia solani and Rhizopus stolonifer. The seeds have a sanitary quality considered regular. All phytopathogens were controlled by essential oil at a concentration of 3 mL Kg-1 of seeds, however, this concentration of essential oil negatively affects the germination power of seeds. For the specific control of Fusarium, seeds of the cultivar BRS Guariba were used, naturally infested with an average incidence of 87%.